Strategi Penerapan Digital Marketing Pada Lembaga Amil Zakat (LAZ) Zakat Sukses - Muhammad Fathoni Yasin; Saputra, Edy (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2023)
This study aims to determine the digital marketing strategy implemented by Zakat Institution the Zakat Sukses so that it can achieve a very good growth rate in the last three years which reached an average of more than 36% per year. The research methodology used is descriptive qualitative which is based on the AISAS (Attention, Interest, Search, Action, & Share) model. The results of this study indicate that Zakat Sukses has effectively integrated in implementing digital marketing in the collection program. The success of this excellent collection is also due to the very effective organizing strategy of